FORECASTING THE WORK OF VENTILATION SYSTEMS OF RESIDENTIAL MULTI-APARTMENT BUILDINGS WITH DECENTRALIZED MECHANICAL AIR DELIVERY - M. A. Krivoshein (Вестник СибАДИ, 2017)
In the article some aspects of forecasting the operation of the ventilation systems of residential multi-apartment buildings with decentralized mechanical air removal and natural inflow are considered. The physical and mathematical models of the ventilation system of a residential multiapartment building with decentralized mechanic air removal and an algorithm for calculating such systems are presented. The results of the calculations of the ventilation system of a two-room apartment on the upper floor of a multi-apartment apartment house and ventilation system of a ten-story apartment building with decentralized mechanical air removal are given.